Evaluation of financial management pattern of the production unit in referral vocational school with adversary model in Yogyakarta Special Region - Ambar Wahyu Astuti; Soenarto Soenarto (Jurnal Pendidikan Vokasi, 2018)
This study aims to determine the effectiveness of the implementation of Referral Vocational School (SMK Rujukan) program in financial management of production units in the DI. Yogyakarta province. This research was an evaluative research which described problem of financial management of production unit at SMK Rujukan. The approach used of this research were mixed methods which combined quantitative and qualitative research. The evaluation model of this research were an adversary model. An adversary evaluation model were an evaluation that seeked to uncover all the important aspects of the program being evaluated. The results showed that of the 5 SMK studied, there is only 1 SMK that had adequate financial management system of production unit, while 4 other SMK not yet adequated. Forms of protection to financial management of production units for SMK in the DI. Yogyakarta province had not been established yet. No school of the 5 schools studied, had implemented a pattern of financial management in accordance with applicable regulations.